INFLUENCE OF ELASTIC BASE ON DYNAMICS OF CONICAL SHELLS OF VARIABLE THICKNESS UNDER IMPULSE LOADING - Orlenko, S.P. (Reports of the National Academy of Sciences of Ukraine, 2024)
The study of vibrations of elastic conical shells of variable thickness is one of the most urgent problems of deformable solid mechanics. The effective bearing capacity of such shells determines their wide application in aviation, rocket building, shipbuilding and many other fields of engineering and construction. To date, significant progress has been made in the study of dynamic processes in elements of conical structures. However, the problems of dynamic interaction of homogeneous and inhomogeneous conical shell structures with elastic media are not sufficiently studied. The finite-difference method was used to analyze dynamic processes in truncated conical shells of variable thickness on an elastic base under the action of a non-stationary load. An integro-interpolation method of constru cting difference schemes over spatial coordinates and an explicit finite-difference scheme of integration over the time coordinate wer e used to create the numerical algorithm.